Removal Lead Ions from Aqueous Solutions by Production of Local Natural Materials from Waste Tea and Coffee as an Adsorbent Material (Comparative Study) - Zahraa Kadhim Abd Al-Hussain, Hayder M. Abdul Hameed, (Pakistan Journal of Medical & Health Sciences, 2022)
In this article, the production of low-cost adsorbents removal of lead from an aqueous solution from tea and coffee waste and a comparison study between them was investigated utilizing a continuous process to explore the kinetic behavior of the created adsorbent. After charring tea and coffee waste, there was a considerable improvement in surface area and other physical properties such as porosity, density, and bulk density. In the continuous system, several parameters such as (bed height, particle size, and flow rate) were tested, and the optimal circumstances (for each experiment) were held constant for the subsequent sets of tests. The optimal circumstances were achieved as follows (bed height=8cm, particle size=250µm, and flow rate 0.5L/hr)and a random set of experiments showed a removal degree efficiency of lead reaching (99 %). As a result, raising bed height and pH will raise the breakpoint value. While reducing the flow rate, initial concentration, and particle size). Increasing the bed height increases the breakpoint value. Particle size will increase the breakpoint as the flow rate decreases.